196k views
16 votes
Help me please. Ooo yuh get it I guess

Help me please. Ooo yuh get it I guess-example-1

2 Answers

2 votes

Answer:

hi

Explanation:

i think 0

because


4a + ( - 4a) = 0


4b + ( - 4b) = 0


4c + ( - 4c) = 0

have a nice day

User TDSii
by
5.0k points
3 votes

Answer: 0

Step-by-step explanation:Let's simplify step-by-step.

4a+4b+4c−4a−4b−4c

=4a+4b+4c+−4a+−4b+−4c

Combine Like Terms:

=4a+4b+4c+−4a+−4b+−4c

=(4a+−4a)+(4b+−4b)+(4c+−4c)

Answer:

=0

User Ben Aubin
by
5.0k points